CONTROL OF DENGUE FEVER: THE ROLE OF NURSES - Naif Khalaf Alotaibi; Mohammed Noor Alasadi; Nawaf Khalaf Alotaibi; Abdulhadi Mishkhas Alotaibi; Fahad Raja Alharthi; Abdulmajeed Nawar Alasadi; Ali Mubarak Al Qarni (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Due fever is a significant public health concern, particularly in tropical and subtropical regions around the world. This essay explores the role of nurses in the control and management of dengue fever, focusing on the importance of medication in treatment strategies. Methods used in controlling the disease will be discussed, as well as the results of current approaches. The essay concludes with a discussion on the challenges and opportunities for improving dengue fever control, emphasizing the crucial role of nurses and medication in the overall management of the disease.